Effects of the speed ratio on the efficiency of planetary mills. Issue 2 (February 2019) - Real, C.; Gotor, F.J.
Abstract: The ignition time (tig ) of the mechanically induced self-sustaining reaction (MSR) process involving the formation of TiB2 from Ti/2B elemental mixtures was used to study the influence of the ratio ( k = -ω v /ω d ) between the rotational speed of the supporting disc ( ω d ) and vials ( ω v ) on the milling efficiency of a Pulverisette 4 planetary mill. The variation of the inverse of the ignition time (1/tig ), which is directly related to the milling power provided by the planetary mill, with the process conditions has shown that it is not possible to find a single k value as optimal independently of the experimental conditions used ( ω d and the ball-to-powder ratio, BPR). Moreover, it was observed that the lowest milling efficiency (longer tig values) was found for k = 1, which is the usual value employed in routine laboratory works. The best efficiencies were found for the larger k values (2.5 or 3). At lower ω d, the shortest tig was obtained for k = 2.5 and at higher ω d for k = 3, independently of BPR.